Endemic mycoses in South Africa, 2010-2020: A decade-long description of laboratory-diagnosed cases and prospects for the future - Rutendo E. Mapengo; Tsidiso G. Maphanga; Wayne Grayson; Nelesh P. Govender (Public Library of Science (PLoS), 2022)
Background Emergomycosis, histoplasmosis, sporotrichosis and blastomycosis are endemic to southern Africa; the first two are AIDS-related mycoses. We described laboratory-diagnosed cases of endemic and imported mycoses in South Africa over a decade and discuss available diagnostic tools, reasons for the current under-estimation of cases and future strategies to improve case ascertainment. Materials and methods We analysed electronic pathology laboratory data from all public laboratories and one large private laboratory in South Africa from 2010-2020. Diagnostic specimens processed at the national mycology reference laboratory were also included. We classified cases as proven, probable and possible based on the method of identification. Results We identified 682 cases, of which 307 were proven, 279 were probable and 96 were possible. Of 307 culture-confirmed cases, 168 were identified by phenotypic methods plus sequencing, 128 by phenotypic methods alone and 11 by direct PCR. Of 279 probable cases, 176 had yeasts observed on histology, 100 had a positive Histoplasma antigen test and 3 a positive pan-dimorphic PCR test. All 96 possible cases had compatible clinical syndrome with inflammatory infiltrates on skin tissue histology. A majority of cases had an unspecified endemic mycosis (207/682, 30.4%), followed by sporotrichosis (170/682, 24.9%), emergomycosis (154/682, 22.6%), histoplasmosis (133/682, 19.5%), blastomycosis (14/682, 2.1%) and talaromycosis (4/682, 0.6%). Conclusions This study reports a relatively low number of cases over a decade considering an estimated large population at risk, suggesting that a substantial fraction of cases may remain undiagnosed. There is a need to increase awareness among healthcare workers and to develop rapid point-of-care diagnostic tools and make these widely accessible. Author summary Emergomycosis, histoplasmosis, sporotrichosis and blastomycosis are serious fungal diseases which occur in southern Africa among people with either healthy or weakened immune systems. These fungal diseases may be missed because they mimic other diseases, occur together with other conditions that mask their presence or are simply not considered by healthcare workers. There are very few available simple diagnostic tests and most African countries do not conduct fungal disease surveillance. We described cases of these fungal diseases, which had been diagnosed in South African laboratories, from 2010-2020. We identified 682 cases, of which 307 were proven, 279 were probable and 96 were possible based on the available clinical and laboratory information. A majority of cases could not be allocated to one of the four disease types and were classified as unspecific endemic mycoses (30.4%). The remainder were sporotrichosis (24.9%), emergomycosis (22.3%), histoplasmosis (19.5%), blastomycosis (2.1%) and a travel-associated infection, talaromycosis (0.6%). We found relatively few cases considering the large population at risk. We believe that this could be due to the above-mentioned issues and insufficient expertise in diagnostic laboratories. There is a need to increase awareness among healthcare workers and to develop rapid point-of-care diagnostic tools and make these widely accessible.